Applying the TBL model to disclose sustainable performance in economic units: applied research in the Kufa Cement Factory - حيدر علي جراد المسعودي; هبة نبيل حميد المسعودي (Iraqi Journal for Administrative Sciences, 2024)
This research aims to implement TBL in economic entities in order to achieving and disclosing sustainable performance. The research concluded that companies' adoption of sustainability reports is generated by the pressure of stakeholders to provide information related to the conservation of economic resources for future generations, significant challenges for companies in how TBL is linked to their operations, as well as the opportunity to increase community support, increase employees' rights, maintain and improve corporate expectations, while there is no International standard for TBL report, there is no measures that comprise each of the three categories of TBL, that can be counted as a strength point because it allows to adapt the overall framework of TBL according to their needs, as well as can be a weak point because the sustainable performance cannot be compared between each other, finally there is a possibility to apply the TBL model in Iraqi companies in order to enhance the direction of transparency and enable them to provide information about their sustainable performance. The research came out with a set of recommendations, drawing the attention of Iraqi legislator, Financial need to care to report sustainable performance and to attach the utmost importance to its impact on the development of the national economy, community development, conservation of environment and economic resources, and the adoption of modern methods and high-level technology is supporting the implementation of the Triple Bottom Line model in many areas, affecting on society and the environment.